Regional Governance of Internal Displacement and Peacebuilding in North Kivu - Keza, Tessah (Université d'Ottawa | University of Ottawa, 2024)
This research paper discusses the failure by regional peacebuilding efforts in North Kivu to produce better conditions for peace and stability over the last ten years. Years of conflict in the eastern provinces of the Democratic Republic of Congo have resulted in one of the worst displacement crises on the globe, with North Kivu being home to 2.5 million internally displaced persons (IDPs) at the end of 2023. Poor governance and recurring violence have allowed this crisis to become protracted, which creates critical challenges for populations in North Kivu and in turn fuels key conflict dynamics that drive armed group proliferation and conflict regeneration. This is despite the presence of regionally supported peace operations over the last several years, which have evidently failed to prevent recurring conflict induced displacement and protect IDPs. This paper therefore studies two regional frameworks on the management of internal displacement, the Protocol on the Protection and Assistance to Internally Displaced Persons, as well as the African Union Convention for the Protection and Assistance of Internally Displaced Persons and examines why they have not been able to address the displacement crisis in North Kivu and the implications this has had for peacebuilding. This analysis concludes that the institutions behind these regional frameworks – the ICGLR and the AU – have been characterised by significant gaps and weaknesses which limit their ability to implement and operationalize their regional principles on managing displacement – resulting in peacebuilding initiatives that not only fail to manage the consequences of displacement in North Kivu, but at times exacerbate the crisis and thereby contribute to conflict regeneration. This indicates that beyond the deficiencies of the state in Kinshasa, the failure to tackle root causes of insecurity in eastern Congo can also be attributed to a crisis of governance at the regional level. Keywords: peacebuilding, regional conflict management, internal displacement